Peran Pondok Pesantren Syaichona Cholil Putri Balikpapan dalam Pembinaan Akhlak Santri - Siti nasim jf; Sriayu, Rita (Indonesia society of applied science, 2025)
Adolescence is a phase of life characterized by significant biological, psychological, social, and spiritual changes, as well as increasingly complex moral challenges in the digital era, making character development essential in Islamic education. This study aims to analyze the role of Pondok Pesantren Syaichona Cholil Putri Balikpapan in nurturing the character of female students through Islamic values-based education. Employing a qualitative case study approach and involving eight informants, data were collected through observation, in-depth interviews, and documentation. The results show that character development is carried out through role modeling by female teachers, habituation of moral behavior, spiritual education through religious activities, and educational social supervision, thereby fostering discipline, responsibility, and moral awareness among students. The main supporting factors are the religious environment and the close relationship between students and ustadzah, while the main obstacle is the diverse backgrounds of the students. This study affirms that pesantren serves as an effective moral ecosystem in shaping the noble character (akhlakul karimah) of Muslim adolescent girls amidst the currents of modernization.